Design of Mechanical Desiccated Coconut - Cari Malem Karo-Karo; Achwil Putra Munir; Nazif Ichwan (Jurnal Rekayasa Pangan dan Pertanian, 2015)
At this time, coconut scraping for taking milk still use squeeze of coconut. Beside that, the coconut use as material to made breads too. Therefore the writer made a desiccated coconut. This research was done by literature study, equipment manufacture, testing and observations of parameters. The parameters observed were the equipment capacity, economics analysis, break event point and the feasibility study using value of internal rate of return and net present value. The capacity of the equipment was 114,07 coconut/hour, Economics analysis was Rp. 354,06/coconut, break event point was 16.927,61 coconut/year, internal rate of return was 43,93 % and the equipment was feasible. Keywords: agricultural machinery, blade., desiccated coconut